1994
DOI: 10.1254/jjp.66.337
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Mixture of Peptidase Inhibitors (Amastatin, Captopril and Phosphoramidon) on Met-Enkephalin-, β-Endorphin-, Dynorphin-(l-13)- and Electroacupuncture-Induced Antinociception in Rats

Abstract: ABSTRACT-The effects of a mixture of three peptidase inhibitors (PIs), amastatin, captopril and phosphoramidon, on methionine-enkephalin (Met-enk)-, j3-endorphin (p-end)-, dynorphin-(1 13) (Dyn) and electroacupuncture (EA)-induced antinociception were compared in rats. EA was performed by passing electric pulses (3 Hz, 0.1-msec duration, for 45 min) through acupuncture needles inserted into the Hoku point. The antinociceptive effect was estimated by the hind paw pressure test. The antinociceptive effects of Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
1
1

Year Published

1998
1998
2011
2011

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 40 publications
1
10
1
1
Order By: Relevance
“…Earlier studies demonstrated that stimulation of acupoint LI4 induced analgesia in humans (20,21,(30)(31)(32), and antinociception in animals (33,34). However, the current results showed no similar orofacial effect of acupoint LI4 in these animals.…”
Section: Discussioncontrasting
confidence: 91%
“…Earlier studies demonstrated that stimulation of acupoint LI4 induced analgesia in humans (20,21,(30)(31)(32), and antinociception in animals (33,34). However, the current results showed no similar orofacial effect of acupoint LI4 in these animals.…”
Section: Discussioncontrasting
confidence: 91%
“…The analgesic effect of EA is largely decreased by blocking the opioid receptors in periaqueductal grey (PAG) matter with naloxone or antibodies against µ- or δ-receptors 11. The microinjection of the mixed peptidase inhibitors of amastatin, captopril and phosphoramidon into the PAG prevents hydrolysis of an enzyme-induced degradation of endogenous opioid peptides, potentiating the effects of acupuncture analgesia 13. In the current study, EA induced analgesic effect was also blocked by naloxone.…”
Section: Discussionmentioning
confidence: 57%
“…Thus, intrathecal Leu-enkephalin failed to produce analgesia in the tail-flick test, even at high doses (100 nmol), but it produced analgesia at low very doses (0.3 nmol) when it was co-injected with peptidase inhibitors (Chen et al, 2007). Another study (Kishioka et al, 1994) found that peptidase inhibitors substantially increased the analgesia produced by Metenkephalin, dynorphin or electroacupuncture. The high susceptibility of enkephalins (Guyon et al, 1979;Hiranuma et al, 1998b) and dynorphins (Hiranuma et al, 1998a;Numata et al, 1988) to peptidase degradation is well-known, and prompted the development of peptidase inhibitors as analgesics (Noble et al, 1992a;Noble et al, 1992b;Noble et al, 1997).…”
Section: Discussionmentioning
confidence: 93%